Old Henry - Blos, Joan W.; Gammell, Stephen (New York Mulberry Books, 1990)
Henry's neighbors are scandalized that he ignores them and lets his property get run down, until they drive him away and find themselves missing him.
Keywords: Neighborliness -- Fiction; Stories in rhyme